Manipulation of quantum information in N@C-60 using electron and nuclear magnetic resonance - Ardavan, A; Morton, J; Benjamin, S; Porfyrakis, K; Andrew, G; Briggs, D; Tyryshkin, A; Lyon, SA (2007)
We review recent progress towards implementing quantum information processing protocols using electron and nuclear magnetic resonance in the molecule N-14@C-60. Using conventional spectrometers, we measure the errors inherent in quantum manipulations of spins. By applying composite pulses, we correct the dominant error to a high degree. Identifying a two qubit computational basis out of the electron and oF nuclear spin levels of N-14@C-60, we implement an ultrafast phase gate on the nuclear qubit by exciting an electron spin transition. (c) 2007 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.